Young students' treatment of synthetic voicing as an interactional resource in digital writing. Issue 3 (3rd July 2022) - Norén, Niklas; Melander Bowden, Helen; Evaldsson, Ann-Carita
ABSTRACT: This multimodal conversation analysis study is part of a larger video ethnographic project that explores the media literacy practices that children develop as they use digital and mobile technologies. The study investigates how Swedish students in grades 3–4 make use of text to speech (TTS) technology as an interactional resource during collaborative writing on iPads in the classroom. The results show that students routinely make use of synthetic voicings to display and claim knowledge about the voiced written units and negotiate writing roles with differing epistemic rights and obligations to assess voicings and practice repair.